The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0052545
|View full text |Cite
|
Sign up to set email alerts
|

Weed or Wheel! fMRI, Behavioural, and Toxicological Investigations of How Cannabis Smoking Affects Skills Necessary for Driving

Abstract: Marijuana is the most widely used illicit drug, however its effects on cognitive functions underling safe driving remain mostly unexplored. Our goal was to evaluate the impact of cannabis on the driving ability of occasional smokers, by investigating changes in the brain network involved in a tracking task. The subject characteristics, the percentage of Δ9-Tetrahydrocannabinol in the joint, and the inhaled dose were in accordance with real-life conditions. Thirty-one male volunteers were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 80 publications
4
55
0
3
Order By: Relevance
“…The weakened feeling of confusion among heavy smokers reflects a greater tolerance to negative symptoms. These effects as felt by occasional smokers are discussed in depth by Battistella et al [26]. Similar effects involving a tolerance mechanism have been found by others and are presented in a recent paper of Theunissen et al [44].…”
Section: μG/l)supporting
confidence: 66%
See 1 more Smart Citation
“…The weakened feeling of confusion among heavy smokers reflects a greater tolerance to negative symptoms. These effects as felt by occasional smokers are discussed in depth by Battistella et al [26]. Similar effects involving a tolerance mechanism have been found by others and are presented in a recent paper of Theunissen et al [44].…”
Section: μG/l)supporting
confidence: 66%
“…The overall design of the study has been described in a previous publication and its supportive information [26]. The study was expanded in order to include regular cannabis smokers.…”
Section: Methodsmentioning
confidence: 99%
“…[15] The imaging sessions determined the timeframe of the one-day experiment. The study was extended to include a similar-sized group of young male heavy cannabis smokers.…”
Section: Methodsmentioning
confidence: 99%
“…Not surprisingly, roadside surveys have demonstrated that driving under the influence of cannabis (DUIC) is a common and widespread occurrence [2][3][4][5]. Cannabis consumption has been shown to have impairing effects on cognitive functions and psychomotor skills related to driving and to be associated with an elevated accident risk [6][7][8][9]. Thus, DUIC has severe implications on global road safety and is considered a serious criminal offense in many countries [10].…”
Section: Introductionmentioning
confidence: 99%